If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(3 + 9x) = 0 (3 * -2 + 9x * -2) = 0 (-6 + -18x) = 0 Solving -6 + -18x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -18x = 0 + 6 Combine like terms: -6 + 6 = 0 0 + -18x = 0 + 6 -18x = 0 + 6 Combine like terms: 0 + 6 = 6 -18x = 6 Divide each side by '-18'. x = -0.3333333333 Simplifying x = -0.3333333333
| (ln(9x+4))-(ln(x))=ln(10) | | W^2+5=36 | | 25x+30=45x+20 | | 4+a+3= | | 15w+17w-5+1=-3w+1-5 | | 2(y+8)=30-5y | | 2(3+9x)= | | -6y+3x^2=y-x+2 | | -5(x-4)=-73 | | 14w+17w-6+5=-5w+5-6 | | 9+10(6a-1)= | | 3b+2p=29.50 | | x+2x-2x+16=180 | | 35-4x=-10 | | (X-1)(9x^2+3x+1)=0 | | x+2x-x+16=180 | | -3(-7w+3)-6w=5(w-1)-8 | | 5N+34=2(1-9N) | | 10-5(6)=20 | | 5.1a+10=71.2 | | 0.25(4x-2)=x-.50 | | 8(x+4)=4(x+8)+4x | | 9x^4+27x^3-13x^2-12x+4=0 | | 10x+2y=54 | | cospix=.5 | | 7(9x-1)=2(9x+1)+846 | | -14+126x=14+84x | | 13x+89=180 | | 2x-(x+7)+9= | | 12n(n+3)+15=396 | | 22=3y+x | | 7(18x-2)=14(6x+1) |